LITHIUM-RICH CLASSICAL CEPHEID V1033 CYG: EVOLUTIONARY STATUS - Udovichenko, S N.; Kovtyukh, V. V.; Keir, L. E. (Одеські астрономічні публікації, 2019)
We investigate evolutional status of cepheid V1033 Cyg in this work, its period of light variation consists 4 d .94 and the star is a real candidate on first crossing of instability stripe (IS) (as well as α of UMi). At first crossing of instability stripe, that lasts all close 1000 years, cepheids demonstrate the rapid increase of period, sometimes is a presence of strong line of lithium 6707 ˚ A. Such objects knows only four in our Galaxy, one of them - V1033 Cyg. During included in a instability stripe amplitude of pulsations headily grows from a zero to some permanent size, and on leaving from (IS) - again falls to a zero. For verifica- tion this phenomenon in the Astronomical observatory of Odesa National University (Ukraine) on the 48-cm telescope AZT-3, equipped by CCD photometer with the optical sensor Sony ICX429ALL, a 1864 measuring of light V1033 Cyg were done in the filter of V and 713 in the filter R, that are partly presented in the Table. 1 and Fig. 2, and fully accessible to address http://cdsarc.ustrasbg.fr/viz-bin/cat. Considerable change of amplitude it is not got by us. The position of cepheid is certain by us in the (IS) - it appeared that star is near her center. In this phase evolutional to development and it must not be observed considerable change of amplitude (color index). The light curves, effective temperature and luminosity of V1033 Cyg are consistent with fundamental mode pulsation for a classical Cepheid on the center of the instability strip.